Design and analysis of amplitude and phase tunable VCO for ISM band application - Zhang, Yuxiang (2015)
Oscillators are an integral part of many electronic systems. With rapid development in the area of Radio Frequency (RF) and wireless communication, the interest in oscillator which generates Local Oscillator (LO) signal has grown rapidly in the last few years. The LO signal is required to down-convert the RF signal to a lower Intermediate Frequency (IF) signal, or vice versa. For typical RF application, LC Voltage-Controlled Oscillator (VCO) is used. It is essential to tune the VCO for an optimized performance due to two reasons. Firstly, the phase noise of the VCO has great effect on the selectivity of the receiver. Secondly, VCO is one of the most power hungry blocks of the transceiver. Hence the power consumption of the transceiver can be reduced significantly by optimizing that of the VCO. Moreover, for transceivers that implement quadrature modulation/demodulation scheme, the phase error and amplitude error of the LO signal can affect the function of the overall performance significantly. With the development and popularity of Wireless Local Area Network (WLAN) and Personal Area Networks (PANs) which operates in the Industrial, Scientific and Medical (ISM) band, it is essential to design VCO with optimized performance for ISM band application. In this thesis, the aim is to explore the VCO's tuning method, both differential and quadrature, to optimize the overall performance. Firstly, a fully integrated hybrid type Automatic Amplitude Calibration (AAC) VCO has been designed and fabricated in 0.18 µm CMOS technology. The operation of the whole loop and the state-dependent nature is analyzed followed by the analysis of important blocks. Based on these analyses, a quantitative transient analysis for the whole loop is performed. A systematic design procedure is proposed according to the relationship explored in the quantitative transient analysis. Secondly, in order to satisfy the need for quadratuer signal generation with good phase noise and phase error performance, a novel in-phase coupling scheme is proposed. The principle of this in-phase coupling scheme is analyzed first, followed by the analysis for possible sources of phase error. Based on this analysis, two novel schemes for phase error tuning are proposed.